2018
DOI: 10.1016/j.coviro.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus assembly and stability

Abstract: Noroviruses are rapidly evolving RNA viruses and are generally known as the main cause of viral gastroenteritis worldwide. Particle stability is of special interest as transmission occurs via the faecal-oral route and virions are able to persist in the environment. Studies on norovirus capsid assembly and disassembly rely mainly on norovirus-like particles. Notably, stability of several human, murine and bovine variants has been investigated revealing distinct patterns of stability and also distinct assembly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 60 publications
2
34
0
Order By: Relevance
“…Although norovirus VLPs have been thought to exist only in T = 3 assemblies, our cryo-EM VLP structures revealed structural polymorphism between and within genogroups in identical buffer conditions (15, 16). Our GI.1 structure is in good agreement with the previous GI.1 crystal structure (0.8-Å rmsd).…”
Section: Resultsmentioning
confidence: 79%
“…Although norovirus VLPs have been thought to exist only in T = 3 assemblies, our cryo-EM VLP structures revealed structural polymorphism between and within genogroups in identical buffer conditions (15, 16). Our GI.1 structure is in good agreement with the previous GI.1 crystal structure (0.8-Å rmsd).…”
Section: Resultsmentioning
confidence: 79%
“…Overlay of Fab A1227 onto the GI.1 capsid structure (Figures 4E and 4F) indicated that other P domains on the assembled norovirus capsid would clash with both heavy and light chains of the Fab, with only minor clashes with the shell domains (Figure 4G), suggesting that structural rearrangements of the P domain could either expose the A1227 binding site or allow binding at a neighboring P domain. Its lack of blockade or neutralizing activity likely results from antibody A1227 only recognizing defects or maturation intermediates (Pogan et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the lack of a good cell cultivation system for human norovirus, studies concerning norovirus stability have relied on the use of surrogates or recombinant capsids, as reviewed by Pogan et al (). MS2 are among the viruses that have been used as surrogates for norovirus.…”
Section: Resultsmentioning
confidence: 99%